Efficient algorithm for online data retrieval with one antenna in wireless networks. (3rd September 2019) - He, Ping; Luan, Shuli
Given a set of requested data items and a set of multiple channels, data retrieval problem is to find a data retrieval sequence for downloading all requested data items from these channels in a reasonable time range. Almost all existing schemes are applied in offline environment that the client can learn prior knowledge of wireless data broadcast, such as the set of broadcast channels and the broadcast time of data items. However, this information is unknown in online data retrieval. So this paper proposes three online algorithms (MRLR, RM and MRM) for solving online data retrieval problem. Compared with the optimal offline data retrieval algorithm, MRLR, RM and MRM algorithms hold ( k ‒ 1), ( log ( k ‒ 1) + k /2 ) and k /2 competitive rate respectively. Through comparison with the competitive rates and experimental results of proposed online algorithms, we observe that the performance of online data retrieval is improved in wireless networks.